Efektivitas Latihan Fisik terhadap Nyeri Dismenore pada Remaja - Kurniawati, Dwi; Nur H, Nitaya Putri (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Dysmenorrhea or menstrual pain is one of the gynecological conditions often experienced during adolescence, significantly disrupting activities and often requiring sufferers to rest and abandon their activities. Objectives: This research was conducted to determine the Effectiveness of Physical Exercise on Dysmenorrhea Pain in Adolescents. Methods: This study is a quasiexperimental study with a Two group Pre and Post Test design, using purposive sampling technique. Subjects: The total sample consisted of 30 adolescent girls experiencing dysmenorrhea, where 15 subjects were given physical exercise and 15 other subjects served as a control group. Each research subject underwent pain degree measurement before and after treatment using VAS. Results: The difference test between group 1 and group 2 using Independent T-test showed a result of p = 0.001 (p<0.05), indicating a difference in effect. Conclusion: The group that received physical training was more effective in reducing the degree of dysmenorrhea pain in adolescents. Keywords: Physical exercise, Pain, Dysmenorrhea